2015
DOI: 10.1002/ajpa.22825
|View full text |Cite
|
Sign up to set email alerts
|

Localized population divergence of vervet monkeys (Chlorocebusspp.) in South Africa: Evidence from mtDNA

Abstract: Objectives Vervet monkeys are common in most tree-rich areas of South Africa, but their absence from grassland and semi-desert areas of the country suggest potentially restricted and mosaic local population patterns that may have relevance to local phenotype patterns and selection. A portion of the mtDNA control region was sequenced to study patterns of genetic differentiation. Materials and Methods DNA was extracted and mtDNA sequences were obtained from 101 vervet monkeys at 15 localities which represent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Analysis of genetic markers—such as sequence variation in mtDNA, chromosome Y, and small sets of autosomal single nucleotide polymorphisms (SNPs) or microsatellites—work well for tracking paternity, understanding genetic relationships within and among populations, and studying molecular phylogeny across species (Chan et al, ; Coetzer, Turner, Schmitt, & Grobler, ; Hasan et al, ; Haus, Roos, & Zinner, ; Mekonnen et al, ; Perelman et al, ; Smith, Mcdonough, & George, ; Turner et al, ). Their utility for discovering the genetic basis of phenotypic variation, however, is limited.…”
Section: Functional Genetic Variation: a Search For A Genetic Basis Omentioning
confidence: 99%
“…Analysis of genetic markers—such as sequence variation in mtDNA, chromosome Y, and small sets of autosomal single nucleotide polymorphisms (SNPs) or microsatellites—work well for tracking paternity, understanding genetic relationships within and among populations, and studying molecular phylogeny across species (Chan et al, ; Coetzer, Turner, Schmitt, & Grobler, ; Hasan et al, ; Haus, Roos, & Zinner, ; Mekonnen et al, ; Perelman et al, ; Smith, Mcdonough, & George, ; Turner et al, ). Their utility for discovering the genetic basis of phenotypic variation, however, is limited.…”
Section: Functional Genetic Variation: a Search For A Genetic Basis Omentioning
confidence: 99%
“…Manuscript to be reviewed should be discouraged. A recent study focusing on South African vervet monkey phylogeography identified mtDNA structuring among populations linked to current and past habitat distributions, geographic barriers, distance and female philopatry (Turner et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…University of the Free State, Biobank and were previously collected byTurner et al (2016b). All DNA extracts were obtained from ear biopsies.…”
mentioning
confidence: 99%
“…Samples from a total of 81 vervet monkeys were included in this study ( Supplementary Table S1), representing nine localities from across the distribution range (Turner et al 2016b) Figure 1A) and eight bioregions / vegetation types. These localities represent significantly different environmental conditions, based on parameters such as the mean annual precipitation, mean annual ambient temperature and maximum annual temperature (Table 1).…”
Section: Samples and Dna Extractionmentioning
confidence: 99%
“…Vervet monkeys also often find their way to primate rehabilitation centres following human primate conflicts (Wimberger et al 2010) and re-introduction of these animals to suitable recipient populations without considering the provenance of the rehabilitated animals should be discouraged. A recent study focusing on South African vervet monkey phylogeography identified mtDNA structuring among populations linked to current and past habitat distributions, geographic barriers, distance and female philopatry (Turner et al 2016b).…”
Section: Introductionmentioning
confidence: 99%